EFEITO DAS β-CICLODEXTRINAS SOBRE PARÂMETROS BIOQUÍMICOS, DO METABOLISMO ENERGÉTICO E DO ESTRESSE OXIDATIVO EM RATOS WISTAR - Oliveira, Amanda Lima de (2012)
Cyclodextrins (CDs) are cyclic oligosaccharides formed by 6 (αCD), 7 (bCD) or 8 (γCD) glucose units with an internal hydrophobic cavity and outside surface hydrophilic. These three derivatives, the b-cyclodextrin (bCD) seems to be the most advantageous for pharmaceutical use for their availability, cavity size and low cost. The CDs have a future quite promising for their properties as greater absorption of drugs through the biological barriers and time of release, however, some types may not be considered non-toxic. The objective of this study was to investigate the intraperitoneal administration of βCD, M-β-CD and HP-ß-CD for 8 weeks with administered dose of 65.65 mg of CDs/kg rats/day, on parameters of biochemical analyzes, enzymes of energy metabolism, enzymes tiolicas sensitive to increase reactive oxygen species and to make this relationship, also evaluate parameters of oxidative stress in cerebral cortex, liver, kidneys and heart of wistar rats. The results showed that for the group treated with βCD there has been a significant increase in serum urea and creatinine levels, indicating nephrotoxicity, however not related to the other parameters. There was also a great reduction in serum levels of iron for the 3 CDs. The heart showed a reduction in the activity of CKmitocondrial and increase for AK by M-β-CD and reduction of CKmit by HP-ß-CD, but showed a reduction in the levels of diclorofluorceina (DCF) to the 3 CDs and protein carbonyl) by βCD. For the rim there was no significant change in comreducao activity of CKmit by HP-β-CD. In liver tissue, the βCD and M-β-CD reduced the activity of PK, but this is not reflected in blood glucose levels. In the cerebral cortex, the βCD reduced the activity of enzymes CK mitochondrial and PK, also reduced TBARS, but increased carbonyl protein. The indices lipidemic reduced reported by other researchers was not observed in this work, because the group of M-β- CD has a significant increase in serum levels of LDL cholesterol, in addition to aspartate aminostransferase AST, albumin, total protein, alkaline phosphatase, sodium, calcium, magnesium and phosphate. Our results indicate that some CDs alter enzymes crucial for energy metabolism, mainly of brain tissue with a reduction in activity and the PK by βCD. If changes in the activity of these enzymes occur in people who use drugs by intraperitoneal route, it is possible that the energy metabolism and brain functioning may be affected causing damage to the tissue. However more studies are needed to elucidate how there was a reduction of serum iron and as the cyclodextrins affect a structure so well protected by blood-brain barrier as the brain.